BAYCAT : how a new hybrid nonprofit model is creating sustainability and driving social change - Isaacs, Andrew M., (SAGE Knowledge. Cases., 2018)
Villy Wang founded BAYCAT in 2004 with an ambitious mission--to end inequality and racism through powerful storytelling. Specifically, Wang wanted to reduce the digital divide. To accomplish that mission, she created a more financially sustainable nonprofit model. BAYCAT (Bayview-Hunters Point Center for the Arts and Technology) is run more like a business than a typical nonprofit. This hybrid model benefits multiple stakeholders including donors, clients, nonprofits, small businesses and local communities. This case explores BAYCAT's unique hybrid model and examines the possibility of replicating it for other socially responsible nonprofits. The BAYCAT example shows the benefits--to multiple stakeholders--of blending aspects of nonprofit and for-profit structures. Also, this case highlights the timely topic of hybrid models with businesses increasingly communicating socially conscious brands.